Sphere‐to‐Multipod Transmorphic Change of Nanoconfined Pt Electrocatalyst during Oxygen Reduction Reaction. Issue 2 (2nd November 2018) - Yang, Juchan; Kang, Dongwoo; Jeon, Yuju; Lee, Jong Hoon; Jeong, Hu Young; Shin, Hyeon Suk; Song, Hyun‐Kon
Abstract: An oxygen reduction reaction (ORR) catalyst/support system is designed to have Pt nanoparticles nanoconfined in a nanodimensionally limited space. Holey crumpled reduced graphene oxide plates (hCR‐rGO) are used as a carbon support for Pt loading. As expected from interparticular Pt‐to‐Pt distance of Pt‐loaded hCR‐rGO longer than that of Pt/C (Pt‐loaded carbon black as a practical Pt catalyst), the durability of ORR electroactivity along cycles is improved by replacing the widely used carbon black with hCR‐rGO. Unexpected morphological changes of Pt are electrochemically induced during repeated ORR processes. Spherical multifaceted Pt particles are evolved to {110}‐dominant dendritic multipods. Nanoconfinement of a limited number of Pt within a nanodimensionally limited space is responsible for the morphological changes. The improved durability observed from Pt‐loaded hCR‐rGO originates from 1) dendritic pod structure of Pt exposing more active sites to reactants and 2) highly ORR‐active Pt {110} planes dominant on the surface. Abstract : Pt nanoconfined within holes of graphene exhibits excellent durability along repeated oxygen reduction. The Ostwald ripening dominant over the surface migration in the nanoconfined situation evolves spherical multifaceted Pt particles to the {110}‐dominant dendritic multipods.